UPAYA PANTI ASUHAN PUTRI AISYIYAH BABAT LAMONGAN SEBAGAI STRATEGI MENCAPAI KEMANDIRIAN FINANSIAL - Rembrant Shella Gustami; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2019)
The background of this study is a financial surplus situation at the Aisyiyah Female Orphanage Babat in the last 4 years. This phenomenon encourages researchers to raise research that discusses the financial independence strategy that is implemented until the manager can fund the needs of the orphanage without prioritizing donation funds. This study uses a qualitative approach with a case study strategy. Data collection is done through interview techniques with relevant parties and related documents. The data analysis technique used is making explanations. The results of this study indicate that Aisyiyah Female Orphanage can be said to be financially independent. Independence is achieved by implementing a number of strategies including conducting several business ventures, implementing an independent financial management system, fostering entrepreneurial spirit of foster children, determining the priority of sources of income and fostering a spirit of sharing with others in foster children.Keywords: financial, strategy, financial independence, Aisyiyah Female Orphanage, Babat